2008
DOI: 10.1016/j.jmb.2008.06.047
|View full text |Cite
|
Sign up to set email alerts
|

Divalent Metal Ion Complexes of S100B in the Absence and Presence of Pentamidine

Abstract: As part of an effort to inhibit S100B, structures of pentamidine (Pnt) bound to Ca 2+ -loaded and Zn 2+ ,Ca 2+ -loaded S100B were determined by X-ray crystallography at 2.15 Å (R free = 0.266) and 1.85 Å (R free = 0.243) resolution, respectively. These data were compared to X-ray structures solved in the absence of Pnt, including Ca 2+ -loaded S100B and Zn 2+ ,Ca 2+ -loaded S100B determined here (1.88 Å; R free = 0.267). In the presence and absence of Zn 2+ , electron density corresponding to two Pnt molecules… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
93
0

Year Published

2010
2010
2015
2015

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 53 publications
(97 citation statements)
references
References 78 publications
4
93
0
Order By: Relevance
“…Numerous studies of Zn binding and crystal structures for zinc-bound S100B, S100A7, and S100A12 are available, but little is known about the Mn-binding properties of S100 proteins (15)(16)(17)46). Analysis of the antimicrobial properties of S100A12 demonstrated that this neutrophil protein is also capable of inhibiting S. aureus growth.…”
Section: Discussionmentioning
confidence: 99%
“…Numerous studies of Zn binding and crystal structures for zinc-bound S100B, S100A7, and S100A12 are available, but little is known about the Mn-binding properties of S100 proteins (15)(16)(17)46). Analysis of the antimicrobial properties of S100A12 demonstrated that this neutrophil protein is also capable of inhibiting S. aureus growth.…”
Section: Discussionmentioning
confidence: 99%
“…Such a short helix is also observed in other Ca 2+ -loaded S100 proteins, for example S100A6 [protein data bank (PDB) entry 1K96], S100A8 (PDB entry 1MR8) or S100A9 (PDB entry 1IRJ) [45][46][47]. The C-terminal, classical EF-hand consists of helix III (52)(53)(54)(55)(56)(57)(58)(59)(60)(61)(62), the Ca 2+ -binding loop (63)(64)(65)(66)(67)(68)(69)(70)(71) and helix IV (72)(73)(74)(75)(76)(77)(78)(79)(80)(81)(82)(83)(84)(85)(86)(87)(88)(89).…”
Section: +mentioning
confidence: 88%
“…-loaded states [4,18,47,[52][53][54][55][56][57][58][59][60]. Interestingly, the Ca 2+ -free structures exhibit a highly similar helix III-helix IV packing, with Leu62 (S100A2 numbering) strictly conserved among these four proteins.…”
Section: +mentioning
confidence: 99%
“…For each compound, a reference 1D WaterLOGSY spectrum of the compound alone and a 1D WaterLOGSY spectrum in the presence of the protein were recorded. The initial setup of the WaterLOGSY experiment was performed on pentamidine, a molecule known to bind S100B at the p53 site with high affinity; [49] this provided an internal control of the reliability of our methodological approach. WaterLOGSY NMR experiments employed a 2 ms selective rectangular 1808 pulse at the water signal frequency and a NOE mixing time of 2 s. (1): [50] K d values in the case of fast exchange between free and bound forms were calculated by plotting the weighted average 1 H and 15 N chemical shifts of affected residues as a function of fragment concentration during the titration, and were fitted considering the one-site binding mode.…”
Section: Chemistrymentioning
confidence: 99%